Proteomics in Chronic Prostatitis: Biomarker Discovery, Molecular Pathways, and Emerging Targets for Precision Medicine - samenezhad, Sina; Allameh, Farzad; Rafighi, Dorna; Ahani, Hasti (Archives of Men's Health, 2025)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common and disabling urological disorder that affects quality of life in men. Despite accounting for most prostatitis cases, its causes remain unclear, involving immune dysregulation, oxidative stress, microbial factors, and epithelial barrier dysfunction. This uncertainty complicates diagnosis and treatment. Proteomics offers a high-throughput approach to identify proteins and pathways involved in CP/CPPS. Recent studies have profiled urine, seminal plasma, prostatic secretions, and serum to uncover biomarkers linked to inflammation, oxidative stress, and microbial virulence. These findings provide insights into molecular endotypes, guide new classifications, and point toward novel therapeutic targets such as cytokine signaling, pyroptosis pathways, and heat shock proteins. Although technical variability and small cohort sizes remain major challenges, integration of proteomics with multi-omics platforms and explainable AI may transform CP/CPPS management by enabling personalized diagnostics and targeted interventions.